A Novel Universal Torque Control of Switched Reluctance Motors for Electric Vehicles - Mahmoud Hamouda; Fahad Al-Amyal; Ismoil Odinaev; Mohamed N. Ibrahim; László Számel (Mathematics, 2022)
Due to their advantages, switched reluctance motors (SRMs) are interesting solutions for electric vehicle (EV) propulsion. However, they have the main drawback of high torque ripple. This paper develops a universal torque control (UTC) technique for SRM that can fulfill all vehicle requirements under a wide range of speeds. The developed UTC involves two different control techniques. It utilizes the direct instantaneous torque control (DITC) strategy in a low speed region, and the average torque control (ATC) strategy in high speeds. The selection of DITC and ATC is made based on their performance regarding torque ripple, torque/current ratio, and efficiency. Moreover, a novel transition control between the two control techniques is introduced. The results show the ability of the proposed UTC to achieve vehicle requirements while obtaining all the benefits of torque control over the possible range of speeds. The proposed UTC provides the best performance regarding minimum torque ripple, maximum torque/current ratio, and maximum efficiency over the whole speed range. The transition control achieves a smooth operation without any disturbances. The transition control helps to simplify the overall control algorithm, aiming to have a feasible and practical UTC without a complicated control structure.